Determinants of soybean market participation by smallholder farmers in Zimbabwe - Zamasiya, Byron; Mango, Nelson; Nyikahadzoi, Kefasi; Siziba, Shephard (Academic Journals, 2014)
This article examines the determinants of soybean market participation by smallholder farmers in Zimbabwe, with a view to identifying key policy entry points for increasing farmer incomes. Market linkages have been identified as key to the successful integration of grain legumes into the smallholder farming systems of southern Africa. Data for this article is derived from a baseline household survey in Guruve district of Zimbabwe. Using a sample of 187 smallholder farmers, we employed the Heckman’s Probit model with sample selection to firstly, identify the factors affecting a farmer’s decision to participate in soybean markets and secondly, evaluate the factors that affect the intensity of a farmer’s participation. Study findings show that the use of inoculants and improved soybean seed varieties are significantly correlated with participating in soybean markets. Results also show that ownership of radios has a positive effect on the household’s decision to participate in the soybean market. Further results show that male-headed households are less likely than female-headed households to participate in soybean markets because legumes are seen as women’s crops in Zimbabwe. We conclude that in order to leverage smallholder farmers’ market participation in soybean markets, it is important to improve access to inoculants and improved soybean seed varieties and improving access to market information. We recommend that authorities could improve access to market information to improve farmers’ decision making on soybeans market participation.